The front-line soldier sees himself and the enemies – a brief outline - Kapphengst, Anatol (Acta Universitatis Lodziensis. Folia Germanica, 2020)
The presented article is an attempt to describe in a synthetic way an own vision of a German front-line soldier of the First World War. It also tries to show an image of some enemies – the French, the British and the Russians. The attempt was made on the basis of recollection material and literary forms created either during or soon after the war. The conclusion is unequivocal – the more contact the authors of the texts had with the opponent, the more balanced image of the enemy they presented in their texts and the less were they prone to overestimate the German soldier. Yet the press material contained a lot of exaggeration. The authors created a haughty and sometimes even superhuman image of the German soldier. At the same time the image of the enemy was inhuman and deserving contempt.